Thromboxane A2 inhibition of SKCa after NO synthase block in rat middle cerebral artery. - McNeish, A; Garland, C (2007)
BACKGROUND AND PURPOSE: NO/prostanoid independent, EDHF-mediated hyperpolarization and dilation in rat middle cerebral arteries is mediated solely by endothelial cell IK(Ca). However, when the NO-pathway is also active, both SK(Ca) and IK(Ca) contribute to EDHF responses. As the SK(Ca) component can be inhibited by stimulation of thromboxane A(2) (TxA(2)) TP receptors and NO has the potential ability to inhibit thromboxane synthesis, we investigated whether TxA(2) might explain loss of functional input from SK(Ca) during NOS inhibition in cerebral arteries. EXPERIMENTAL APPROACH: Rat middle cerebral arteries were mounted in a wire myograph. Endothelium-dependent responses to the PAR2 agonist, SLIGRL were assessed as simultaneous changes in smooth muscle membrane potential and tension. KEY RESULTS: Responses were obtained in the presence of L-NAME as appropriate. Inhibition of TP receptors with either ICI 192,605 or SQ 29,548, did not affect EDHF mediated hyperpolarization and relaxation, but in their presence neither TRAM-34 nor apamin (to block IK(Ca) and SK(Ca) respectively) individually affected the EDHF response. However, in combination they virtually abolished it. Similar effects were obtained in the presence of the thromboxane synthase inhibitor, furegrelate, which additionally revealed an iberiotoxin-sensitive residual EDHF hyperpolarization and relaxation in the combined presence of TRAM-34 and apamin. CONCLUSIONS AND IMPLICATIONS: In the rat middle cerebral artery, inhibition of NOS leads to a loss of the SK(Ca) component of EDHF responses. Either antagonism of TP receptors or block of thromboxane synthase restores an input through SK(Ca). These data indicate that NO normally enables SK(Ca) activity in rat middle cerebral arteries.